Kinerja Manajemen Rantai Pasok Mangga Gedong Gincu Di Perusahaan Dagang (Pd) Sari Buah Kecamatan Majalengka Kabupaten Majalengka - Afifudin, Ifan; Sihabbudin, Firman (Jurnal SUTASOMA (Science Teknologi Sosial Humaniora), 2024)
Sari Buah Trading Company (PD.) is a supplier of various fruits to several supermarkets, with one of its main commodities being Gedong Gincu mangoes. This study aims to describe the overall supply chain and evaluate its supply chain management performance at Sari Buah Trading Company. A case study method was employed, collecting data from January to December 2019. The research utilized the Food Supply Chain Networking (FSCN) method for descriptive supply chain depiction and the Supply Chain Operational Reference (SCOR) method to evaluate management performance across all entities involved. Respondents included individuals engaged in the supply chain, including partner farmers, Sari Buah Trading Company, and retail partners. The findings indicate that the Gedong Gincu mango supply chain at Sari Buah Trading Company operates effectively. Although supply chain management performance across all levels is generally satisfactory, there exists a gap-parity condition in reliability attributes, necessitating performance improvements in this area.